A robust broadband fat‐suppressing phaser T2‐preparation module for cardiac magnetic resonance imaging at 3T. Issue 3 (24th March 2021) - Arn, Lionel; van Heeswijk, Ruud B.; Stuber, Matthias; Bastiaansen, Jessica A. M.
Abstract : Purpose: Designing a new T2 ‐preparation (T2 ‐Prep) module to simultaneously provide robust fat suppression and efficient T2 preparation without requiring an additional fat‐suppression module for T2 ‐weighted imaging at 3T. Methods: The tip‐down radiofrequency (RF) pulse of an adiabatic T2 ‐Prep module was replaced by a custom‐designed RF‐excitation pulse that induces a phase difference between water and fat, resulting in a simultaneous T2 preparation of water signals and the suppression of fat signals at the end of the module (a phaser adiabatic T2 ‐Prep). Numerical simulations and in vitro and in vivo electrocardiogram (ECG)‐triggered navigator‐gated acquisitions of the human heart were performed. Blood, myocardium, and fat signal‐to‐noise ratios and right coronary artery vessel sharpness were compared against previously published adiabatic T2 ‐Prep approaches. Results: Numerical simulations predicted an increased fat‐suppression bandwidth and decreased sensitivity to transmit magnetic field inhomogeneities using the proposed approach while preserving the water T2 ‐Prep capabilities. This was confirmed by the tissue signals acquired in the phantom and the in vivo images, which show similar blood and myocardium signal‐to‐noise ratio, contrast‐to‐noise ratio, and significantly reduced fat signal‐to‐noise ratio compared with the other methods. As a result, the right coronary artery conspicuity was significantly increased. Conclusion: A novel fat‐suppressing T2 ‐Prep method was developed and implemented that showed robust fat suppression and increased vessel sharpness compared with conventional techniques while preserving its T2 ‐Prep capabilities.